Managing Uncertainty in Time Expressions for Virtual Assistants - Rong, Xin; Fourney, Adam; Brewer, Robin N.; Morris, Meredith Ringel; Bennett, Paul (Proceedings of the 35th Annual CHI Conference on Human Factors in Computing Systems (CHI '17), 2017)
“Remind me to get milk later this afternoon.” In communications and planning, people often express uncertainty about time using imprecise temporal expressions (ITEs). Unfortunately, modern virtual assistants often lack system support to capture the intents behind these expressions. This can result in unnatural interactions and undesirable interruptions (e.g., having a work reminder delivered at 12pm, when out at lunch, because the user said “this afternoon”). In this paper we explore existing practices, expectations, and preferences surrounding the use of ITEs. Our mixed methods approach employs surveys, interviews, and an analysis of a large corpus of written communications. We find that people frequently use a diverse set of ITEs in both communication and planning. These uses reflect a variety of motivations, such as conveying uncertainty or task priority. In addition, we find that people have a variety of expectations about time input and management when interacting with virtual assistants. We conclude with design implications for future virtual assistants.
Best Paper Honorable Mention